Pola Pendidikan Islam dalam Pendidikan Anak - M.Pd.I., Masita (Jurnal Munaqasyah, 2019)
Abstract: Patterns of Islamic education in children's education, it is fitting for Muslims to pay attention to children's education and individual development to achieve the title "best people" as described by Allah SWT in the Qur'an Surah Ali-Imran (3): 110. Education of children starting from their respective homes, when children begin to speak, fathers are obliged to teach to say the tauhid sentence: Laa ilaaha illa Allah. And when he is six years old he must be taught to carry out obligatory prayers. At that age, formal education began. In the science of child development psychology is a period or phase that must be passed by each individual human to get to the phase of maturity. The first years of age 0-6 years are referred to as the mother's school period because almost all educational guidance efforts plus care and maintenance take place in the family, where maternal activities have a large contribution to the smooth process of growth and development of children. Therefore as a parent, a wise mother will give positive and continuous attention and care to the developments that occur in her children, from the age of fighting until before her maturity. One tangible form of parental attention to children's development is the provision of various early education to their children. This paper attempts to discuss the pattern of Islamic education in children's education. A concept of Islamic education that must be applied to children from an early age. The concept of Islamic education in children's education is the theoretical foundation of Islamic education which starts from the time of his mother's womb.